The Quest for the Holy Grail : Efficient and Equitable Fiscal Consolidation in India - Abdallah, Chadi (IMF Working Papers; Working Paper, 2015)
Achieving fiscal consolidation without undermining growth and poverty-reduction efforts is a key policy challenge in many countries. Using India as an illustration, this paper shows how a mix of well-designed taxation and spending policies can help address these challenges. On the tax side, the analysis focuses on increasing consumption taxes on goods with negative consumption externalities. On the spending side, some of the additional revenues from the tax reform are allocated to scaling up key social transfer programs. Substantial additional gains are possible if the increased social transfers can be accompanied by improved targeting.